Triglyceride glucose index and its combination with the Get with the Guidelines-Heart Failure score in predicting the prognosis in patients with heart failure - Han, Su; Wang, Chuanhe; Tong, Fei; Li, Ying; Li, Zhichao; Sun, Zhaoqing; Sun, Zhijun (Frontiers in Nutrition, 2022)
Abstract Background: Heart failure (HF) is associated with generalized insulin resistance (IR). Recent studies have demonstrated that triglyceride-glucose (TyG) is an effective alternative index of IR. However, the relationship between the TyG index and in-hospital mortality in patients with HF is unclear. In the present study, we aimed to clarify the association between the TyG index and in-hospital mortality in HF patients. Methods: A retrospective study consisting of 4411 patients diagnosed with HF from 2015–2018 was conducted. All-cause mortality during hospitalization was the primary endpoint. The association between the TyG index and in-hospital mortality was assessed using logistic regression analysis. Results: The risk of in-hospital mortality was significantly associated with increased TyG index (OR: 1.886, 95% CI: 1.421–2.501, p<0.001) under logistic regression with multivariable adjustment. When divided into three groups based on the TyG index, Tertile 3 demonstrated significantly higher in-hospital mortality than the other two Tertiles (OR: 2.076, 95% CI: 1.284–3.354, p=0.001). Moreover, the TyG index improved the prediction efficiency of the Get with the Guidelines-Heart Failure (GWTG-HF) score (Absolute integrated discrimination improvement =0.006, p<0.001; Category-free net reclassification improvement =0.075, p=0.005). In subgroup analysis, the TyG index exhibited similar predictive performance of in-hospital mortality when groups were stratified based on type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD). Conclusions: TyG is a potential index for predicting in-hospital mortality in patients with HF, independent of T2DM or CAD status. The TyG index may be combined with the GWTG-HF score to further improve its predictive efficacy.